RETRACTED: Alhakamy et al. Thymoquinone-Loaded Soy-Phospholipid-Based Phytosomes Exhibit Anticancer Potential against Human Lung Cancer Cells. Pharmaceutics 2020, 12, 761 - Nabil A. Alhakamy; Shaimaa M. Badr-Eldin; Usama A. Fahmy; Nabil K. Alruwaili; Zuhier A. Awan; Giuseppe Caruso; Mohamed A. Alfaleh; Ahmed L. Alaofi; Faris O Arif; Osama A. A. Ahmed; Adel F. Alghaith (MDPI AG, 2024)
The journal retracts the article, "Thymoquinone-Loaded Soy-Phospholipid-Based Phytosomes Exhibit Anticancer Potential against Human Lung Cancer Cells" [...]